PRICE EARNING RATIO, PRICE CASH FLOW RATIO, PRICE SALES RATIO DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2017-2020) - Dany Prayoga; Suripto Suripto; M Iqbal Harori (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the effect of Price Earning Ratio, Price Cash Flor Ratio, Price Sales Ratio and Company Size on Stock Returns in Banking Companies listed on the IDX. The data in this study is secondary data which includes stock price data, earnings per share, operating cash flow, number of outstanding shares, cash flow per share, asset sales, total assets and stock prices of 9 banking companies listed on the IDX for the 2017-2020 period. . The sample in this study amounted to 47 samples taken using purposive sampling technique. In this study, the data were analyzed using multiple regression with the results showing that simultaneously Price Earning Ratio, Price Cash Flow Ratio, Price Sales Ratio and Company Size had a significant effect on Stock Return with an R Square value of 27.7%. Meanwhile, partially shows that the variable Price Earning Ratio, Price Sales Ratio and Company Size does not have a significant effect and for the variable Price Cash Flow Ratio has a significant effect on Stock Return.